Taâ€™thÄ«r Taá¹bÄ«q á¹¬arÄ«qah al-Ghinaâ€™ fÄ« Tarqiyah IstÄ«Ê¿Äb al-MufradÄt al-â€˜Arabiyah - Fauziah, Silvia; Anas, Al Baihaqi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The problem in this research that students are less enthusiastic about learning Arabic, and teachers do not use good and interesting learning methods. Teachers do not use modern methods, but only use books, boards and pens. So the students got bored and students' motivation in learning Arabic is low. The research aims to the application of the singing method affects the promotion of vocabulary proficiency among fifth-grade students in the public elementary school 1 Agam. The method used by the researcher is the descriptive quantitative research method. It is the use of statistical formulas that correspond to existing problems. Meanwhile, to find out the effect of applying the singing method on studentsâ€™ vocabulary pick-up in public elementary school 1 Agam, the researcher used a t-test formula at 1% and 5% levels. It means at 40 df 1% level = 2.423 and 5% level = 2.021. Because of the significance level of the calculation t compared to the table t, the null hypothesis is rejected and the alternative hypothesis is accepted, so the conclusion is that there is an effect of applying the singing method in vocabulary picking for fifth-grade students in public elementary school 1 Agam.Â Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù„Ù… ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„Ù…Ø¹Ù„Ù…Ø© Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØØ¯ÙŠØ«Ø©ØŒ ÙˆÙ„ÙƒÙ† ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„ÙƒØªØ§Ø¨ØŒ ÙˆØ§Ù„Ø³Ø¨ÙˆØ±Ø©ØŒ ÙˆØ§Ù„Ù‚Ù„Ù… ÙÙ‚Ø·ØŒ Ø¯Ø§ÙØ¹ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù†Ø®ÙØ¶. Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù†Ø®ÙØ¶. ØØªÙ‰ ÙŠØ´Ø¹Ø± Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¨Ø§Ù„Ù…Ù„Ù„ ÙˆÙŠÙ‚Ù„ Ø¯Ø§ÙØ¹ Ø§Ù„Ø·Ù„Ø§Ø¨ Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ ØªØØ¯ÙŠØ¯ ØªØ£Ø«ÙŠØ± ØªØ·Ø¨ÙŠÙ‚ Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ØºÙ†Ø§Ø¡ Ø¹Ù„Ù‰ Ø²ÙŠØ§Ø¯Ø© Ø¥ØªÙ‚Ø§Ù† Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„Ø®Ø§Ù…Ø³ ÙÙŠÂ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠØ© Ø§Ù„Ø¹Ø§Ù…Ø© 1 Ø¢ØºØ§Ù…. Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø°ÙŠ Â ØªØ³ØªØ®Ø¯Ù…Ù‡ Ø§Ù„Ø¨Ø§ØØ«Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙ…ÙŠ Ø§Ù„ÙˆØµÙÙŠ. ÙˆÙ‡Ùˆ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ØµÙŠØº Ø§Ù„Ø¥ØØµØ§Ø¦ÙŠØ© Ø§Ù„ØªÙŠ ØªØªÙˆØ§ÙÙ‚ Ù…Ø¹ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„Ù‚Ø§Ø¦Ù…Ø©. ÙˆÙÙŠ Ø§Ù„ÙˆÙ‚Øª Ù†ÙØ³Ù‡ØŒ Ù„Ù…Ø¹Ø±ÙØ© ØªØ£Ø«ÙŠØ± ØªØ·Ø¨ÙŠÙ‚ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØºÙ†Ø§Ø¡ ÙÙŠ Ø¥ØªÙ‚Ø§Ù† Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠØ© Ø§Ù„Ø¹Ø§Ù…Ø© 1 Ø¢ØºØ§Ù…ØŒ Ø§Ø³ØªØ®Ø¯Ù…Øª Ø§Ù„Ø¨Ø§ØØ«Ø© ØµÙŠØºØ© Ø§Ø®ØªØ¨Ø§Ø± t Ø¹Ù†Ø¯ Ù…Ø³ØªÙˆÙŠØ§Øª 1Ùª Ùˆ 5Ùª. ÙŠØ¹Ù†ÙŠ Ø°Ù„Ùƒ Ø¹Ù†Ø¯ 40 dfÂ Â Ù…Ø³ØªÙˆÙ‰ 1Ùª = 2.423 ÙˆÙ…Ø³ØªÙˆÙ‰ 5Ùª = 2.021. Ø¨Ø³Ø¨Ø¨ Ù…Ø³ØªÙˆÙ‰ Ø¯Ù„Ø§Ù„Ø© Ø§Ù„ØØ³Ø§Ø¨ t Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨Ø§Ù„Ø¬Ø¯ÙˆÙ„ tØŒ ÙŠØªÙ… Ø±ÙØ¶ ÙØ±Ø¶ Ø§Ù„ÙØ±Ø¶ÙŠØ© Ø§Ù„ØµÙØ±ÙŠØ© ÙˆÙŠØªÙ… Ù‚Ø¨ÙˆÙ„ Ø§Ù„ÙØ±Ø¶ÙŠØ© Ø§Ù„Ø¨Ø¯ÙŠÙ„Ø©ØŒ ÙˆØ¨Ø§Ù„ØªØ§Ù„ÙŠ ÙØ¥Ù† Ø§Ù„Ø§Ø³ØªÙ†ØªØ§Ø¬ Ù‡Ùˆ Ø£Ù† Ù‡Ù†Ø§Ùƒ ØªØ£Ø«ÙŠØ±Ø§Ù‹ Ù„ØªØ·Ø¨ÙŠÙ‚ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØºÙ†Ø§Ø¡ ÙÙŠ Ø¥ØªÙ‚Ø§Ù† Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª. ÙÙ†ØªÙŠØ¬Ø© Ø§Ù„Ø¨ØØ« Ø£Ù† Ø§Ù„ÙØ±Ø¶ÙŠØ© Ø§Ù„ØµÙØ±ÙŠØ© (Ho) Ù…Ø±Ø¯ÙˆØ¯Ø© ÙˆØ§Ù„ÙØ±Ø¶ÙŠØ© Ø§Ù„Ø¨Ø¯Ù„ÙŠØ© (Ha)Ù…Ù‚Ø¨ÙˆÙ„Ø©. Ø£Ù† ÙŠÙˆØ¬Ø¯ Ø§Ù„ÙØ±Ù‚ Ø¨ÙŠÙ† Ø§Ù„ÙØµÙ„ÙŠÙ† Ø¯Ù„ ÙØ±Ù‚ ØÙ‚ÙŠÙ‚ÙŠ Ø¨Ø¹Ø¯ Ø§Ø³ØªØ¹Ù…Ø§Ù„ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØºÙ†Ø§Ø¡ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø®Ø§Ù…Ø³.